DI BALIK KETERBATASAN KOGNITIF: STRATEGI PEDAGOGIS DALAM PEMBELAJARAN SHALAT BAGI SISWA TUNAGRAHITA - Azzah Aafiena Berlian Virdaus; Saifuddin; Syaikhu Rozi (STKIP Subang, 2026)
This study is motivated by the importance of implementing adaptive pedagogical strategies when teaching the Shalat(Islamic prayer) to students with intellectual disabilities. Cognitive limitations and diverse learning characteristics require educators to employ flexible teaching strategies tailored to each student's needs. The study aims to describe the adaptive pedagogical strategies implemented by educators, identify the challenges faced and the solutions adopted, and analyze the impact on students' Shalat proficiency at SLB Sabilillah Cukir. A qualitative approach with a case study design was employed. Data were gathered through observation, interviews, and documentation involving the school principal, the Islamic Religious Education teacher, and the classroom teacher. Data analysis followed the Miles and Huberman model, with validity verified through source and technique triangulation. The findings indicate that adaptive pedagogical strategies are implemented through demonstrations, the cultivation of worship habits, individual guidance, material repetition, and motivation tailored to the students' characteristics. Challenges encountered include limitations regarding cognition, memory, communication, and motor skills, as well as a lack of worship practice at home. These challenges are addressed through individualized instruction, the use of simple language, consistent habituation, direct demonstration, and collaboration with parents. The implementation of these strategies improves students' proficiency in prayer movements and recitations, fosters worship habits, and boosts student self-confidence in accordance with their individual potential.